Empowering women farmers through collective action: a case study of Khanizpur Hamlet, Odisha - Baruah, S.; Mohanty, Samarendu; Rola, A.C. (Informa UK Limited, 2022)
Vulnerable landless women farmers face the dual challenge of small farm size and illegality of land tenancy. These smallholders face a lack of bargaining power in input and output markets and economic non-viability of technology adoption. We piloted a collective action model of organizing agriculture production work called "Small Farmers Large Field" with 35 landless tenant women farmers in Khanizpur village, Odisha. Within an embedded mixed method design, the study included the collection of both qualitative and quantitative data. In this QUAL + quan design, the qualitative dataset assumes the primary role. The results indicate that the per acre net income that represented a loss of INR 2,831 in the previous wet season changed to a positive profit of INR 15,065. Much of the increase in net income was due to the 60% increase in yield. Several factors including the use of good-quality seeds and adoption of improved practices contributed to such yield improvement. Apart from the monetary benefits, the collective action among farmers resulted in many non-monetary benefits such as improved knowledge on technology and production practices, stronger social network and civic engagement, and efficient use of water. In addition, farmers had a significant amount of time saving in different field operations.